Morphology and electrical properties of electrochemically synthesized pyrrole-formyl pyrrole copolymer - Gholami, M.; Nia, P.M.; Alias, Y. (Elsevier, 2015)
A direct electrochemical copolymerization of pyrrole-formyl pyrrole (Py-co-FPy) was carried out by oxidative copolymerization of formyl pyrrole and pyrrole in LiClO4 aqueous solution through galvanostatic method. The (Py-co-FPy) copolymer was characterized using Fourier-transform infrared spectroscopy (FT-IR), field emission scanning electron microscope (FESEM), energy-filtering transmission electron microscope (EFTEM), thermal gravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The FESEM images showed that the synthesized copolymer had a hollow whelk-like helixes structure, which justifies the enhancement of charge transportation through the copolymer film. Cyclic voltammetry studies revealed that the electrocatalytic activity of synthesized copolymer has improved and the surface coverage in copolymer enhanced 1.6 times compared to polypyrrole alone. Besides, (Py-co-FPy) copolymer showed 2.5 times lower electrochemical charge transfer resistance (R-ct) value in impedance spectroscopy. Therefore, this copolymer has a strong potential to be used in several applications such as sensor applications. (C) 2015 Elsevier B.V. All rights reserved.